2013
DOI: 10.1039/c3nr03009a
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature crystallisation of mesoporous TiO2

Abstract: Conducting mesoporous TiO 2 is gaining rapidly in importance for the manufacture of green energy applications. To optimise performance, its porosity and crystallinity must be carefully fine-tuned. To this end, we have performed a detailed study on the temperature dependence of TiO 2 crystallisation in mesoporous films. Crystal nucleation and growth of initially amorphous TiO 2 derived by hydrolytic sol-gel chemistry is compared to the evolution of crystallinity from nanocrystalline building blocks obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 45 publications
0
28
1
Order By: Relevance
“…The presence of seed reduced the crystallization temperature from 127.2°C for the powder mixtures without the seed to 126.5 and 122.4°C when 5 and 10 wt.% seed were added, respectively. This temperature reduction is rather moderate when compared to that reported by Xie et al [16] and Kohl et al [17] in their annealed amorphous TiO 2 , revealing that the presence of seed particles played only a minor role in our solvothermal crystallization of TiO 2 . This difference is likely to stem from the relatively quick liquid transportation involved in the solvothermal treatment, which provides an enhanced atomic transportation than that of the diffusion-controlled annealing crystallization in solid particles, leading to the difference in crystallization temperature.…”
Section: Methodscontrasting
confidence: 64%
See 2 more Smart Citations
“…The presence of seed reduced the crystallization temperature from 127.2°C for the powder mixtures without the seed to 126.5 and 122.4°C when 5 and 10 wt.% seed were added, respectively. This temperature reduction is rather moderate when compared to that reported by Xie et al [16] and Kohl et al [17] in their annealed amorphous TiO 2 , revealing that the presence of seed particles played only a minor role in our solvothermal crystallization of TiO 2 . This difference is likely to stem from the relatively quick liquid transportation involved in the solvothermal treatment, which provides an enhanced atomic transportation than that of the diffusion-controlled annealing crystallization in solid particles, leading to the difference in crystallization temperature.…”
Section: Methodscontrasting
confidence: 64%
“…They attributed the seeded crystallization to the formation of fortuitous nuclei when the seed nanoparticles were in contact with the amorphous ones. Kohl et al [17] also reported an enhanced anatase nucleation along with a pronounced grain growth by the incorporation of crystalline TiO 2 seed. In this study, we aim to address the relative importance between the amorphous-to-anatase transformation and the grain growth of anatase TiO 2 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…34,35 TiO 2 nanocrystals were synthesized via a nonhydrolytic sol−gel chemistry route 36 which was modified to compatibilize the nanocrystals with the solvent mixture used to dissolve the polymer and sol. 37 The components were subsequently combined with varying amounts of TiO 2 , which led to a hybrid solution that was processed into a thin film. Following temperature annealing to condense the inorganic matrix, the organic components were removed by reactive ion etching in an oxygen plasma.…”
mentioning
confidence: 99%
“…41 In the presence of phosphorus dendrimer DG 4 , a lowest E a of 15.38 kJ.mol -1 was obtained ( Figure S12, Supporting Information). The activation energies calculated for the titanium mineralization using a branch-mimicking dendrimer (M 4 ) or in the absence of any phosphorus additive (M 5 ), both of them have led to an amorphous titanium dioxide at 60°C, were found to be respectively equal to 47.72 and 49.22 kJ.mol -1 ( Figure S12, Supporting Information).…”
Section: Stability and Crystal Growth Of Anatase Nanocrystalsmentioning
confidence: 99%